Translanguaging Practices in Second Language Education and Their Implications for Multilingual Language Policy - Melissa Tan Wei Ling (LIER: Language Inquiry & Exploration Review, 2026)
Purpose: This study examined the predictive relationship between translanguaging practices and second language learning outcomes among university students in Singapore. Subjects and Methods:  A quantitative cross-sectional design was employed among 260 university students in Singapore. Participants were selected purposively based on their experience with English-medium or second language education. Data were collected using a structured five-point Likert-scale questionnaire measuring Translanguaging Practices and Second Language Learning Outcomes. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4. Results: The measurement model demonstrated strong reliability and validity, with indicator loadings above 0.80, AVE values of 0.715 and 0.754, and HTMT of 0.741. Translanguaging practices significantly and positively predicted second language learning outcomes (β = 0.672, t = 16.390, p < 0.001), with a substantial effect size (f² = 0.823). The model explained 45.2% of the variance in learning outcomes (R² = 0.452) and demonstrated predictive relevance (Q² = 0.326). These findings indicate that multilingual practices can function as pedagogical resources in higher education. Conclusions: Translanguaging practices represent a predictor of second language learning outcomes in Singaporean higher education, supporting the integration of multilingual resources into pedagogy.